Morphological evolution of zinc oxide originating from zinc hydroxide carbonate - Sigoli, F. A. [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. [UNESP] (Elsevier, 1997)
Zinc oxide can be obtained by thermal decomposition of hydrozincite, a topochemical reaction. This work reports the relation between zinc oxide morphology and the precursor zinc hydroxide carbonate precipitation time. The morphological evolution was monitored by SEM, IR and XRD. Zinc oxide obtained from initially precipitated hydrozincite consists of porous spherical aggregates and shows a single Zn-O IR vibrational band. At longer periods of precipitation time the aggregates were transformed into spherulitic-shaped zinc oxide particles showing the Zn-O split vibrational band. X-ray patterns show that the hexagonal zinc oxide phase is substantially increased as a function of hydrozincite precipitation time. © 1997 Elsevier Science S.A.
Keywords: Hydrozincite; Morphology; Zinc hydroxide carbonate; Zinc oxide; Carbonates; Crystal structure; Infrared spectroscopy; Precipitation (chemical); Pyrolysis; Scanning electron microscopy; X ray diffraction